Controle hierárquico distribuído com separação de atribuições para paralelismo de UPS - Jank, Henrique (2021)
This work presents a distributed hierarchical control strategy applied to the parallelism of UPSs. A dynamic approach with separation of concerns is proposed for the secondary control, where a named grid forming inverter is responsible for restoring the amplitude and frequency of the output voltage, while the remaining inverters, named as grid supporting, are responsible for enhancing the long-term power sharing. This strategy aims to minimize the trade-off between voltage regulation and power sharing through the secondary control, which uses a low bandwidth communication link. For the primary controller, the resistive droop control with the virtual resistance concept is employed to accomplish short-term power sharing. Simple design guidelines for the secondary controllers are provided based on simplified models developed in the work. Extensive experimental results are obtained from two 500 VA prototypes in order to evaluate the feasibility of the proposed strategy, which demonstrate its good performance, where the amplitude and power sharing errors remained below 1% and 2%, respectively, for all evaluated load conditions.